The Effects of Crop Raiding on Household Food Security in the Albertine Rift: A Case Study of Queen Elizabeth National Park, Western Uganda - Barirega, Akankwasah; Buyinza, Mukadasi; Kansiime, Frank; Isabirye, Gilbert Basuta (Human Dimensions of Wildlife, 2010)
We examined the effects of crop raiding by wild animals on household food security of the people in two sub counties adjacent to Queen Elizabeth National Park in Western Uganda. Data were collected from 541 households using a questionnaire and focus group discussions in a controlled and blocked household survey in Kichwamba and Nyakiyumbu sub counties in the Districts of Bushenyi and Kasese, respectively. Food security was examined by using dietary diversity indices. Crop raiding dominated by elephants resulted in 14% annual reduction in household food security of park-adjacent communities. It is recommended that a crop raiding mitigation fund be established to maintain elephant trenches and building capacity for local people to manage crop raiding and a multidisciplinary agriculture extension be started in the area to increase agricultural production and household incomes in order to prevent heavy dependency on protected area resources.
Keywords: food security; crop raiding; Albertine Rif t; Queen Elizabeth National Park; Uganda